The Impact of The SWOM Strategy on The Achievement of Male Students in Preparatory Stage an Developing their Mathematical Power - Abdulkareem Jameel, Sahar (Opción, 2019)
The aim of the present research is to identify (the impact of the strategy of SOM (Swom) in the achievement of fourth grade students and the develop- ment of sports power on them). In light of the objective of the research, the researcher formulated zero hypotheses, and to verify the research objective and hypotheses, the researcher chose a preparatory Khalid bin Walid for boys of the Directorate of Education Salah al-Din Department of Educa- tion Tikrit deliberately as a place to conduct its experiment, and randomly selected two divisions (B, C) to represent the two research groups The ex- perimental and control group was randomly assigned to represent the ex- perimental group to study according to the SWOM strategy. Division (B) became the control group to study according to the usual method. Student group includes Experimental (32) students and the control group compris- ing (32) were verified parity between the two sets of search in the IQ test variables, the chronological age of the students measured in months, aca- demic achievement for parents, former academic achievement of students in mathematics, mathematical test force. The experiment was applied in the first semester of the academic year (2018-2017) and the researcher taught the two research groups themselves by five classes per week for each group.The researcher prepared on the two research groups after verifying the sin- cerity of its content, by presenting it to the specialists, and applied to a sur- vey sample to ensure the clarity of its paragraphs and to ensure its stability using the alpha-Kronbach method, as well as its psychometric properties (discriminatory force, difficulty factor, effectiveness of alternatives). As for the measurement of mathematical strength, the researcher prepared a test consisting of (10) paragraphs, the researcher confirmed the validity of his paragraphs after being presented to the specialists and applied to the exploratory sample to find psychometric characteristics (discrimination factor). The researcher also used a number of statistical methods, includ- ing the T-test of two independent samples (test-t) to reward the two groups and to know the significance of the difference between them and the Alpha Kronbach equation to calculate the coefficient of stability for the test of achievement and the test of mathematical strength and the square of Kay to check the equivalence of the two research groups in the academic achieve- ment of parents. 1. The experimental group students who studied using the Swom strategy outperformed the control group students who studied in the normal way by the achievement of statistically significant achievement at the significance level (0.05). 2. The experimental group students who studied using the Swom strategy outperformed the control group students who studied in the normal way by testing the mathematical strength at the level of 0.05). 3. There is a statistically significant difference between the scores of the experimental group students who studied using the Swom strategy on the pre and post mathematical strength test. In this light, the researcher reached a number of recommendations and proposals.